Hystrix in Greek - Witczak, Krzysztof Tomasz (Studia Ceranea, 2013)
Dictionaries of the Ancient Greek language distinguish only two or three different meanings of the Greek word ὕστριξ. The present author analyses all the contexts and glosses where the word in question appears. On the basis of his own analysis he assumes that dictionaries of Ancient Greek should contain as many as seven different semantems: I. ‘swine bristle’, II. ‘swine leather whip, the cat, used as an instrument of punishment’, III. ‘porcupine, Hystrix cristata L.’, IV. ‘hedgehog, Erinaceus europaeus L.’, V. ‘sea urchin’, VI. ‘badger, Meles meles L.’; VII. ‘an unclearly defined animal’.